Role of filtration membrane in bioreactor for wastewater treatment - Ramakrishnan Narayanasamy (2008)
Filtration membrane application in wastewater treatment industry is getting much attention and becoming more prevalent these days, driven mainly by the increasing necessity to reuse water. The operational data available from the existing installations and the recent advances in membrane technology are causing the initial scepticism to give way to optimism. As the advantages of membrane application in wastewater treatment like reduced space requirements, reduced sludge production etc. are being increasingly realised by the industry, membrane related treatment system applications are due for exponential growth in the coming years, especially in the industrial wastewater treatment systems.